Periodyki późnej epoki stanisławowskiej jako źródła dla historyka prawa ustrojowego. O „Gazecie Narodowej i Obcej” oraz „Pamiętniku Historyczno-Polityczno-Ekonomicznym” - Tarnowska, Anna (Czasopismo Prawno-Historyczne, 2018)
The following contribution is devoted to the informative and political journalism of the Stanislaw II Augustus era. It may constitute a secondary source for the research of law historians, particularly in the studies of the history of the system of government. Among other things, the article refers to “The Index of Bills” (Polish Seriarz Projektów do Prawa) which may be regarded as the first Polish legal periodical. Special attention is devoted to two landmark journals of the Great Sejm period, namely “The National and Foreign Newspaper” (Polish Gazeta Narodowa i Obca) and “The Historical, Political and Economical Journal” (Polish Pamiętnik Historyczno-Polityczno-Ekonomiczny), as well as to their editors. “The National and Foreign Newspaper” became the most popular contemporary periodical (1791-1792) which promulgated the subject matter of the proceedings and the effects of the legislative work of the Great Sejm. Moreover, it was shaping political sympathies of its readers in a relatively subtle way. On the other hand, particular commitment to politics and social policy was expressed by Piotr Świtkowski who was the editor and the publisher of “The Historical, Political and Economical Journal” (1782-1792). The end of both publications was brought about by the legal acts of the Targowica Confederation.